Der Einfluß der orographischen Situation auf die Windverhältnisse im Spiegel der Vegetation, dargestellt an Beispielen aus dem Val Maroz (Bergell), aus dem Oberengadin und vom Pru del Vent (Puschlav) - Holtmeier, Friedrich-Karl (ERDKUNDE, 1971)
Windshaped trees and - in high-mountain areas with a cold winter climate - the pattern of the bottom layer of the vegetation, which is mainly formed by the windinfluenced distribution of the snow-cover in winter, can be used as fairly good indicators of the prevailing and most effective winds. The map published in this paper is based on observations, which were chiefly obtained during fieldwork on the alpine timber-line in eastern Graubünden. It shows that because of the special orographical situation of the valleys under consideration, which favours the inflow of air masses of the atmospheric circulation, the influence of these gradient-winds on the vegetation is much more effective than that of the local breezes (valley-breezes etc.) being a quite characteristic phenomenon of these fairly continental valleys in general. Furthermore in comparison to the; other localities mentioned in this paper it indicates the quite special situation of the Oberengadin. In contrast to those which are strongly influenced by winds from the Northwest, the upper part of the Oberengadin, which is fairly protected against these air-currents by high mountain-ridges, is dominated by winds from the Southwest which can easily follow the course of the valley. Only within the Champagna-area, where the valley is a very broad one, does it come under the rule of the northwest-winds as well, which can become effective there even on the bottom of the valley because of the orographic situation. The increasing influence of these winds within this region proof of which may be derived from the physiognomy of the vegetation proves that the winds coming from the Northwest are more effective than those from the Southwest, due to the greater frequency and intensity (see the compass-cards in the map) of the northwestern aircurrents.